High-performance diamond radiation detectors produced by lift-off method. (18th April 2016) - Shimaoka, Takehiro; Kaneko, Junichi H.; Tsubota, Masakatsu; Shimmyo, Hiroaki; Watanabe, Hideyuki; Chayahara, Akiyoshi; Umezawa, Hitoshi; Shikata, Shin-ichi
Abstract: For stable semiconductor detector operation under harsh environments, an ideal single-crystal diamond without a charge trapping centre is required. For this study, a self-standing single-crystal CVD diamond was fabricated using a lift-off method. The reduction of charge trapping factors such as structural defects, point defects, and nitrogen impurities, was attempted using 0.2% of low-methane concentration growth and using a full metal seal chamber. A high-quality self-standing diamond with strong free-exciton recombination emission was obtained. Charge collection efficiencies were 100.1% for holes and 99.8% for electrons, provided that and . Energy resolutions were 0.38% for both holes and electrons. We produced a high-performance diamond radiation detector using the productive lift-off method.